Persistent Hypogonadotropic Hypogonadism in Men After Severe Traumatic Brain Injury: Temporal Hormone Profiles and Outcome Prediction. Issue 4 (July 2016) - Barton, David J.; Kumar, Raj G.; McCullough, Emily H.; Galang, Gary; Arenth, Patricia M.; Berga, Sarah L.; Wagner, Amy K.
Abstract : Objective: To (1) examine relationships between persistent hypogonadotropic hypogonadism (PHH) and long-term outcomes after severe traumatic brain injury (TBI); and (2) determine whether subacute testosterone levels can predict PHH. Setting: Level 1 trauma center at a university hospital. Participants: Consecutive sample of men with severe TBI between 2004 and 2009. Design: Prospective cohort study. Main Measures: Post-TBI blood samples were collected during week 1, every 2 weeks until 26 weeks, and at 52 weeks. Serum hormone levels were measured, and individuals were designated as having PHH if 50% or more of samples met criteria for hypogonadotropic hypogonadism. At 6 and 12 months postinjury, we assessed global outcome, disability, functional cognition, depression, and quality of life. Results: We recruited 78 men; median (interquartile range) age was 28.5 (22-42) years. Thirty-four patients (44%) had PHH during the first year postinjury. Multivariable regression, controlling for age, demonstrated PHH status predicted worse global outcome scores, more disability, and reduced functional cognition at 6 and 12 months post-TBI. Two-step testosterone screening for PHH at 12 to 16 weeks postinjury yielded a sensitivity of 79% and specificity of 100%. Conclusion: PHH status in men predicts poor outcome after severe TBI, and PHH can accurately be predicted at 12 to 16 weeks.